2009
DOI: 10.1007/s11606-009-1182-7
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia Recovery; Discrepancies in Perspectives of the Radiologist, Physician and Patient

Abstract: BACKGROUNDChest radiographs are often used to diagnose community-acquired pneumonia (CAP), to monitor response to treatment and to ensure complete resolution of pneumonia. However, radiological exams may not reflect the actual clinical condition of the patient.OBJECTIVETo compare the radiographic resolution of mild to moderately severe CAP to resolution of clinical symptoms as assessed by the physician or rated by the patient.DESIGNProspective cohort study.PARTICIPANTSOne hundred nineteen patients admitted bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 17 publications
(17 reference statements)
1
62
2
Order By: Relevance
“…Although radiologic criteria are commonly used in assessing response to infectious disease therapy, radiologic improvement can frequently lag behind clinical improvement, and routine radiographic follow-up of all infections is not always necessary. For example, in a study of clinical and radiographic follow-up of patients with community-acquired pneumonia, 28 clinical cure was observed in 93% of patients after 10 days of follow-up, whereas radiographic resolution was noted in only 31% of patients. In fact, several weeks or even months may be required before chest radiography or computed tomography shows complete resolution of an infiltrate.…”
Section: Assessment Of Response To Treatmentmentioning
confidence: 99%
“…Although radiologic criteria are commonly used in assessing response to infectious disease therapy, radiologic improvement can frequently lag behind clinical improvement, and routine radiographic follow-up of all infections is not always necessary. For example, in a study of clinical and radiographic follow-up of patients with community-acquired pneumonia, 28 clinical cure was observed in 93% of patients after 10 days of follow-up, whereas radiographic resolution was noted in only 31% of patients. In fact, several weeks or even months may be required before chest radiography or computed tomography shows complete resolution of an infiltrate.…”
Section: Assessment Of Response To Treatmentmentioning
confidence: 99%
“…1 Recovery is further prolonged in individuals requiring hospital admission for treatment of their illness. 2,3 Previous studies have shown that between 35-86% of patients report at least one CAP-related symptom 1 month after their index hospital admission.…”
Section: Introductionmentioning
confidence: 99%
“…This sends back to the difficulty in diagnosing pneumonia in elderly patients with comorbid diseases and complex clinical scenarios, due to atypical clinical presentation, low sensitivity of chest radiograph for detecting pulmonary infiltrates, poor correlation between radiological evolution of pulmonary infiltrates and actual clinical conditions. 1,[25][26][27] For instance, it is not always easy to ascertain that a pulmonary infiltrate is new or changed so that it can be unequivocally attributed to a recent-onset pneumonia, rather than to a previous pulmonary infection, congestive heart failure, pulmonary fibrosis or other lung diseases. 25,27 The second issue is the identification of patients who may have MDR pathogens as pneumonia etiology.…”
Section: Discussionmentioning
confidence: 99%
“…1,[25][26][27] For instance, it is not always easy to ascertain that a pulmonary infiltrate is new or changed so that it can be unequivocally attributed to a recent-onset pneumonia, rather than to a previous pulmonary infection, congestive heart failure, pulmonary fibrosis or other lung diseases. 25,27 The second issue is the identification of patients who may have MDR pathogens as pneumonia etiology. Current guidelines recommend to treat hospitalized patients with either a respiratory fluoroquinolone alone or with a combination of a third-generation cephalosporin plus a macrolide.…”
Section: Discussionmentioning
confidence: 99%